THERE AL COST OF MORTGAGE LENDING AND THE WAY TO ITS ACCESSIBILITY - Nikolay I. Kornilov; Vladimir S. Mkhitaryan (Статистика и экономика)
The article considers the availabilityof mortgage loans to the population,estimated nominal and real value of the mortgage. Describes the current patternand proposes a way to improve it.